Faktor-Faktor Yang Mempengaruhi Efektivitas Pengelolaan Keuangan Daerah - Subadriyah Subadriyah; Lailatul Khafiza (Accounting Study Program, Faculty of Economics and Business, 2018)
Based on Permendagri No. 13 of 2006 effectiveness is defined as the achievement of program results with predetermined targets, namely by comparing expenditures with results. Effectiveness is the success of an organization in achieving the planned goals. This study aims to determine the factors that influence the effectiveness of regional financial management. The factors studied include three independent variables, namely the government's internal control system, the competence of human resources, and the regional financial accounting system.The data used is primary data. Data was collected by distributing questionnaires to the head of the finance department and staff in the finance department at the OPD Jepara Regency, totaling 41 OPD. So that the total questionnaires distributed were 82 questionnaires. The sampling technique was done by simple random sampling. The method of analysis used multiple linear regression analysis. The results showed that (a) SPIP had a significant positive effect on the effectiveness of regional financial management, (b) SAKD had a significant positive effect on the effectiveness of regional financial management, (c) HR competence had a significant positive effect on the effectiveness of regional financial management, and (d) simultaneously SPIP, SAKD and HR competencies affect the effectiveness of regional financial management